Konsep Pendidikan Karakter Kitab Taisir Al-Khalaq Prespektif Fungsi Manajemen “POAC” - Toha Ma'sum (JIEM: Journal of Islamic Education and Manajemen, 2021)
The character of a nation is needed as a characteristic and capital in the development and progress of the nation. The character building of the community begins through a process carried out through formal and non-formal education in which the character building proes begin early, adolescence, even in adult humans. The deterioration and incompatipatipatiacy of character with the identity of the nation, will be problematic for the nation. If we pay attention to this, the reality in our country lately character, moral or moral problems become a very visible problem and require very serious attention. Various forms, models and concepts have been implemented, but do not appear to have met the maximum results. A concept of character education, moral or moral, has actually been widely studied, implemented, but nevertheless there are many concepts of character education that are actually widely studied and applied, but not widely known and taught in the world of education. The Taisīr al-Khalāq is one of the books that describe character education. Although the book already contains the concept of character education, but because of its composition that has different characteristics with today's works, especially those containing character education that has mostly been used in Indonesia, there are still many people in general do not know more about the book, even though it is one of the study books in boarding schools, especially salafiyah-based, and has even applied what is in the book. The concept of Character Education in Taisīr al-Khalāq Perspective management function "POAC" can be concluded that 1) Planning, namely by realizing all the gifts of God in the form of various potentials that have before looking for knowledge for students. 2) Organizing, namely with the form of proper subject sorting and class class class class class. 3) Actuating, namely by motivating teachers and students through the encouragement to apply some of the existing adab in the book 4) Controlling, namely by avoiding things that can eliminate the understanding of the lessons that have been obtained, as well as keeping the classroom stable and conducive.